Hot electron effects in AlGaN/GaN HEMTs during hard-switching events. (November 2021) - Minetto, Andrea; Modolo, Nicola; Meneghini, Matteo; Zanoni, Enrico; Sayadi, Luca; Sicre, Sébastien; Deutschmann, Bernd; Häberlen, Oliver
Abstract: This work contains an investigation of hot-electrons effects in GaN transistors during a hard-switching event by means of wafer-level measurements and TCAD mixed-mode hydrodynamic simulations. The latter reveals the presence of hot electrons at the passivation/barrier interface during commutation. Trapping in this location can explain the measured on-state resistance increase during switching operation and leads to a redistribution of the lateral electric field in the two-dimensional electron gas, which in return modulates the hot electron injection process. Highlights: Wafer-level measurements and TCAD hydrodynamic simulations are presented Hot electrons trapping is the main cause for Ron increase during hard-switching Hot electrons trapping takes mainly place at the passivation/barrier interface Interface trapping leads to a redistribution of the lateral electric field in the 2DEG Trapping concentrates at the drain edge after extended hard-switching operation